Pengaruh Pelaksanaan Praktik Kerja Nyata dan Informasi Pekerjaan Terhadap Kesiapan Kerja Siswa Pada Program Keahlian Teknik Konstruksi dan Properti di SMKN 2 Surabaya - Rizki Kurniawan; Purwo Mahardi (Jurnal Kajian Pendidikan Teknik Bangunan, 2025)
This research aims to examine how the relationship between real work practices and job information has an impact on the work readiness of students who take part in the Construction and Property Engineering skills program at SMK Negeri 2 Surabaya. The influence of this relationship occurs partially or simultaneously. This research applies a quantitative approach and is classified as ex-post facto research. Class XII students of the crime scene expertise program in the 2024/2025 academic year are the research subjects. Collecting data using a data interpretation questionnaire was carried out using descriptive and parametric statistics, as well as multiple regression and simple regression tests using a significance level of 5%. The research results show that (1) real work practices influence students' work readiness and the regression line equation Y = 28.530 + 0.307X1 is obtained, the effective contribution is 6.91%. (2) Job information influences work readiness and the regression line equation Y = 39.231 + 0.364X2 is obtained, the effective contribution is 15.69%. (3) Real work practices and job information influence work readiness and the regression line equation Y = 20.367 + 0.248X1 + 0.333X2 is obtained. Overall an effective contribution of 22.6% is given, and other factors not included in this research contribute 77.4%.